ENHANCING MSME MARKETING PERFORMANCE IN NORTH SUMATERA PROVINCE THROUGH E-MARKETING AND INNOVATION - Christine Loist; Loist Abdi Putra; Kevin Indajang; Lenny Dermawan Sembiring; Acai Sudirman (Jurnal Manajemen dan Bisnis Performa, 2026)
This research aims to analyze the influence of E-marketing, product innovation and market orientation on the marketing performance of MSMEs in Sumatra Province. The research method used was quantitative with a survey approach, where data was collected through questionnaires distributed to 170 MSME respondents from various business sectors. The research results show that E-marketing has a positive and significant effect on the marketing performance of MSMEs, because the use of digital media has been proven to be able to expand market reach. Product innovation also has a significant influence, where creativity in design, quality and product development drives increased competitiveness. In addition, market orientation has a positive effect on marketing performance, because the ability of MSMEs to understand consumer needs and anticipate competitors' movements can increase the effectiveness of marketing strategies. The implications of this research emphasize the importance of increasing digital capacity, encouraging sustainable product innovation, and strengthening market orientation for MSME players. Thus, support from the government and related institutions is urgently needed, especially in terms of digital marketing training, facilitation of market research, and access to technology to strengthen the competitiveness of MSMEs in the era of global competition.